Assessing the public health impact of using poison center data for public health surveillance. (3rd July 2018) - Wang, Alice; Law, Royal; Lyons, Rebecca; Choudhary, Ekta; Wolkin, Amy; Schier, Joshua
Abstract: Context: The National Poison Data System (NPDS) is a database and surveillance system for US poison centers (PCs) call data. The Centers for Disease Control and Prevention (CDC) and American Association of Poison Control Centers (AAPCC) use NPDS to identify incidents of potential public health significance. State health departments are notified by CDC of incidents identified by NPDS to be of potential public health significance. Our objective was to describe the public health impact of CDC's notifications and the use of NPDS data for surveillance. Methods: We described how NPDS data informed three public health responses: the Deepwater Horizon incident, national exposures to laundry detergent pods, and national exposures to e-cigarettes. Additionally, we extracted survey results of state epidemiologists regarding NPDS incident notification follow-up from 1 January 2015 to 31 December 2016 to assess current public health application of NPDS data using Epi Info 7.2 and analyzed data using SAS 9.3. We assessed whether state health departments were aware of incidents before notification, what actions were taken, and whether CDC notifications contributed to actions. Discussion: NPDS data provided evidence for industry changes to improve laundry detergent pod containers safety and highlighted the need to regulate e-cigarette sale and manufacturing. NPDS data were used to improve situational awareness during the 2010 Deepwater Horizon oil spill. Of 59 health departments and PCs who responded to CDC notifications about anomalies (response rate = 49.2%), 27 (46%) reported no previous awareness of the incident, and 20 (34%) said that notifications contributed to public health action. Conclusions: Monitoring NPDS data for anomalies can identify emerging public health threats and provide evidence-based science to support public health action and policy changes.